Analysis of the possibility of using the thermal water available in the city of Łódź for energy purposes - Noga, Bogdan (Instal, 2023)
The article presents an analysis of the possibilities of obtaining thermal water water in the city of Łódź. The temperature and yield of thermal water, depending on the depth of the aquifer, were estimated. Efficiency depending on the depth of the aquifer. Then the article presents an analysis of the possibilities of using thermal water in the production of electricity and heat. energy production and heat production. the possibilities of feeding geothermal heat into the municipal heat network were also analysed. geothermal heat was also analysed for the municipal district heating network in both the CHP plant and heat plant variants. CHP plant and district heating plant. Finally, the possibility of supplying geothermal heat to a recreational facility geothermal heat to a recreational facility with year-round swimming pools. all year round.
Keywords: geothermal; geothermal installation; geothermal borehole; geothermal heat